PREFERENSI MASYARAKAT TERHADAP PROGRAM KAMPUNG TEMATIK DI KOTA SEMARANG - Nana Karida Tri Martuti (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2017)
Semarang is the Capital of Central Java Province which administratively consist of 16 districts and 117 sub-district. Thematic Kampong is part of “GERBANG HEBAT” Program which is an innovation of Semarang City Government to deal with basic need compliance problems, particularly to improve the housing environment quality of the poor and basic infrastructure of housing. This research aims to describe the community preference to the Thematic Kampong in their environment (local authority, BPD, social institution, RT, RW, Karang Taruna and PKK, social figure, and other stakeholders); to describe the community preference to the Programs of Thematic Kampong as the basic needs fulfillment of the community in thematic kampong area; to describe participation and concern of the community to the Thematic Kampong Program in their area and what factors that influence the community preference to the Thematic Kampong Program in Semarang. It conducted at 10 Thematic Kampong in 2016 and 6 Thematic Kampong in 2017. Sampling method used was proportionate stratified random sampling. This technique conducted in accordance with the objectives and conditions of the existing population. The data collection of this research was conducted used some instruments including questionnaire, field survey guide sheet, interview guide and supporting document. The result of the research showed that the community preferences for Thematic Kampong have good value (2-2,5) to better (3-3,5). It was based on the results of questionnaires, interviews and field observations on the implementation of Thematic Kampong Program in 16 sub-district. These results indicated the diversity of assessment and usefulness of the program existence in where the thematic program implemented. The Thematic Kampong Program has not yet benefited economically for the community. The existing programs were for education and ecosystems (infrastructure / physical).